Leveraging social media for enhanced SME performance in the restaurant industry: a case study of Penang, Malaysia / Tisya Farida Abdul Halim ... [et al.] - Abdul Halim, Tisya Farida; Jamaluddin, Raziff; Abdullah, Nuraini; Zahari, Mohd Khairulnizam; Kamaruddin, Nur Syuhadah; Subramanian, Bannu (UiTM Cawangan Perlis, 2025)
This study investigates the impact of social media marketing on the performance of small and medium-sized enterprises (SMEs) in the restaurant industry in Penang. The primary aim is to explore how different social media platforms, content quality, and posting frequency influence key performance indicators such as service quality ratings and reviews. Employing a quantitative research design, the study collected data through surveys distributed to SME restaurant owners, co-owners, managers, workers, and others in Penang. Analysis revealed a significant positive correlation between strategic social media marketing and enhanced SME performance, with notable improvements in service quality ratings and customer reviews. The findings highlight the importance of high-quality, engaging content and optimal post-timing in maximizing customer interaction and business outcomes. These insights suggest that SMEs in Penang's restaurant industry can achieve a competitive edge and sustainable growth by effectively leveraging social media marketing strategies. The study contributes to the existing body of knowledge by providing empirical evidence on the effectiveness of tailored social media marketing strategies for SMEs, offering practical implications for business owners and policymakers. Future research could explore the integration of social media with other marketing elements and the impact of emerging digital tools on SME performance.